Analisis Bentuk Dan Karakteristik Pengembangan Ruang Terbuka Hijau (RTH) Taman Kota Petrosea Kabupaten Mimika - Irsa Febrianti Wanenda; Lazarus Ramandei; Marsal Arung Lamba (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
This study analyzes the morphological form and development characteristics of the Petrosea City Park green open space in Mimika Regency, Central Papua. Using qualitative descriptive-analytical methods, this research examines road patterns, spatial configurations, and architectural elements as well as the physical, economic, and socio-cultural characteristics of park development. The results show that the park implements a radial pattern centered on a roundabout with clear hierarchical zoning, integrating Kamoro cultural landmarks through bronze statues. However, infrastructure limitations and underutilized economic potential indicate the need for integrated development to optimize the function of green open spaces in the context of mining cities in Eastern Indonesia.